Planning of Smart Microgrids with High Renewable Penetration Considering Electricity Market Conditions - Hakimi, Seyed M.; Bagheritabar, Hamed; Hasankhani, Arezoo; Shafie-khah, Miadreza; Lotfi, Mohamed; Catalão, João P. S. (IEEE, 2019)
In this paper, a new method for optimal sizing of distributed generation (DG) is presented in order to minimize electricity costs in smart microgrids (MGs). This paper presents a study of the effect of wholesale electricity market on smart MGs. The study was performed for the Ekbatan residential complex which includes three smart MGs considering high penetration of renewable energy resources and a 63/20 kV substation in Tehran, Iran. The role of these smart MGs in the pool electricity market is a price maker, and a game-theoretical (GT) model is applied for their bidding strategies. The objective cost function considers different cost parameters in smart MGs, which are optimized using particle swarm optimization (PSO). The results show that applying this method is effective for economic sizing of DGs.
Keywords: optimal sizing; PSO; renewable energy system; smart microgrid; fi=Sähkötekniikka|en=Electrical Engineering|